2011
DOI: 10.1007/s00595-010-4414-x
|View full text |Cite
|
Sign up to set email alerts
|

Sinusoidal obstruction syndrome compromises liver regeneration in patients undergoing two-stage hepatectomy with portal vein embolization

Abstract: Sinusoidal obstruction syndrome inhibits FRL hypertrophy after PVE and induces postoperative liver failure. Therefore, an alternative strategy is needed to perform TSH safely in the presence of SOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…Meanwhile, oxaliplatin and irinotecan were reported to induce severe liver injury known as sinusoidal obstruction syndrome and steatohepatitis, respectively, and to impair liver regeneration [12,22,23]. Additionally, in the present study, a history of chemotherapy containing these drugs was indicated as a strong negative predictive factor (regression coefficient: −21.2).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Meanwhile, oxaliplatin and irinotecan were reported to induce severe liver injury known as sinusoidal obstruction syndrome and steatohepatitis, respectively, and to impair liver regeneration [12,22,23]. Additionally, in the present study, a history of chemotherapy containing these drugs was indicated as a strong negative predictive factor (regression coefficient: −21.2).…”
Section: Discussionmentioning
confidence: 68%
“…Previous PVE studies demonstrated that FLR volume increased by 20-50% within a 3- to 7-week interval between PVE and hepatectomy [5,6,7,8]. However, various conditions, including hepatitis, cholestasis, and chemotherapy, are reported to affect remnant liver hypertrophy [7,9,10,11,12]. Meanwhile, 10-20% of the cases become unresectable after such an interval because of tumor progression or insufficient remnant liver hypertrophy [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas 16 SD seems to have a clear inhibitory effect on hypertrophy [126], chemotherapy has no effect on liver regrowth [121,127]. Moreover, patients with NASH show a trend towards less post-PVE liver volume gain compared to patients with normal liver function [126].…”
Section: Enlarging Of Future Remnant Liver Volumementioning
confidence: 97%
“…40 Several studies have associated sinusoidal injury and steatohepatitis with compromised liver regeneration as well as increased morbidity following hepatic resection. [41][42][43][44] …”
Section: Liver-related Factorsmentioning
confidence: 98%